Safety assessment of corroded jacket platform considering decommissioning event - Kim, D.K. (Universiti Malaysia Pahang, 2017)
Continuous assessment of aged offshore structures is becoming extremely important to avoid any hazardous consequences throughout their design life. In Malaysian waters where most of the offshore structures are jacket platforms, it was found that many of these structures are currently operating beyond their design life. With continuous corrosion taking place, structural reliability and operation will be affected. Therefore, for the safety evaluation, this study focuses on the reassessment of an existing aged jacket platform in Malaysian waters pertaining to corrosion effect. In this study, pushover analysis was carried out to determine the ultimate strength of the corroded jacket platform by quantifying the reserve strength ratio value. Two different time-dependent corrosion wastage models were used in the present study to simulate the corrosion behaviour at the splash zone of the jacket platform. It was observed that average corrosion condition relatively simulated the calm waters of Malaysia and by applying this corrosion, the jacket platform can withstand the environmental load acting on it. The results developed in the present study will be useful for future study in predicting and modelling corrosion tolerance of jacket platforms in Malaysian waters. © 2017, Universiti Malaysia Pahang.